Lexicon-based sentiment analysis in texts using Formal Concept Analysis. - Ojeda Hernández, Manuel; López-Rodríguez, Domingo; Mora-Bonilla, Ángel (Elsevier, 2023)
In this paper, we present a novel approach for sentiment analysis that uses Formal Concept Analysis (FCA) to create dictionaries for classification. Unlike other methods that rely on pre-defined lexicons, our approach allows for the creation of customised dictionaries that are tailored to the specific data and tasks. By using a dataset of tweets categorised into positive and negative polarity, we show that our approach achieves a better performance than other standard dictionaries.
Keywords: Emociones - Análisis; Análisis del discurso; Formal Concept Analysis (FCA); Lógica de Simplificaciones (LS); Minería de Texto; Análisis de Sentimientos; Deducción automática; Métodos de clausura